Produção de leite, leite residual e concentração hormonal de vacas Gir × Holandesa e Holandesa em ordenha mecanizada exclusiva - Porcionato, MAF; Negrao, J. A.; Lima, MLP (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2005)
In a machine milking system in which calves were not present, oxytocin concentration (OT), cortisol release (CORT), milk yield and residual milk were evaluated for cows of three genetic groups: 1/2Gir x 1/2Holstein (n=6, genetic group F2), 1/4Gir x 3/4Holstein (n=6, genetic group F3) and Holstein (n=6, genetic group H). Group H had higher milk yield than groups F2 and F3, whereas OT was similar among groups. The increase in OT during milk-ing was greater for H and F3 than for F2. Residual milk for F2 was' higher than for F3 and H. The CORT for F2 was higher than for cows of the other two genetic groups. Cows from F2 and F3 were more stressed than H cows during machine milking, but the Gir x Holstein groups did release suffficient OT to induce an effective milk letdown response.
Milk yield, residual milk, oxytocin concentration and cortisol release in Holstein and Gir x Holstein cows machine milked without stimulus from a calf
Keywords: cattle; behavior; milk ejection; stress